Combined exposure to non-antibiotic pharmaceutics and antibiotics in the gut synergistically promote the development of multi-drug-resistance in Escherichia coli. (31st December 2022) - Shi, Danyang; Hao, Han; Wei, Zilin; Yang, Dong; Yin, Jing; Li, Haibei; Chen, Zhengshan; Yang, Zhongwei; Chen, Tianjiao; Zhou, Shuqing; Wu, Haiyan; Li, Junwen; et al.
ABSTRACT: The gut microbiota represents an important reservoir of antibiotic-resistant bacteria (ARB), which poses a significant threat to public health. However, little is known about the emergence of ARB in the gut after the combined exposure to antibiotics and non-antibiotic pharmaceutics. Here, Escherichia coli, a common opportunistic pathogen in the gut microbiota, was exposed to the antidepressant duloxetine (2.5 µg/L–25 mg/L) and/or chloramphenicol (6 µg/L–4 mg/L). The resistant strains were isolated to determine the minimum inhibition concentration (MIC) of 29 antibiotics. Then, genome-wide DNA sequencing, global transcriptomic sequencing, and real-time quantitative polymerase chain reaction were performed to quantify the synergy between duloxetine and chloramphenicol. Combined exposure synergistically increased the mutation frequency of chloramphenicol resistance by 2.45–9.01 fold compared with the independent exposure. A combination index reaching 187.7 indicated strong duloxetine and chloramphenicol synergy. The resultant mutants presented heritable enhanced resistance to 12 antibiotics and became ARB to eight antibiotics. Furthermore, combined exposure significantly increased the transcriptomic expression of acrA, acrB, and marA in E. coli, and generated a more robust oxidative stress response. Together with the occurrence of DNA mutations in marR in the mutants, stronger triggers to the AcrAB-TolC transport system and the MlaFEDB ABC transporter via reactive oxygen species (ROS)-induced mutagenesis, verified by gene knockout, contributed to the synergistic enhancement of antibiotic resistance in the combined exposure group. Regardless of whether their formation was induced by duloxetine, chloramphenicol, or their combination, the E. coli mutants showed 1.1–1.7-fold increases in the expression levels of acrA, acrB, acrZ, mdtE, and mdtF . This pattern indicated that the mutants shared the same resistance mechanisms against chloramphenicol, involving the improved efflux pumps AcrAB-TolC and mdtEF . Our findings demonstrated that antibiotics and non-antibiotic pharmaceutics synergistically accelerate the evolution of ARB and may enhance their spread.